The Evaluation of Quality Engineering for Supply Chain Operations in Khan Dhari Silo / Case Study - Hardan Sultan*, Muhammad; Attia Khalaf, Batool (Journal of Economics and Administrative Sciences, 2024)
The study aims to search for mechanisms to improve the supply chain operations in the silo of Khan Dhari by applying the requirements of quality engineering and focusing on the axes of design, human engineering and value engineering, which are among the most important axes concerned with quality engineering in the silo.The case study approach was relied upon as an approach that helps in the comprehensive and in-depth analysis of the research problem, and the researcher relied on checklists in collecting and analyzing data. The research problem is summarized in the main question (there are failures and stops in the process of receiving the wheat crop, and there is no analysis of the processes of transporting the wheat crop from the processing sources to the storage stage, through circulation. From transportation, weighing and storage tools, and there is no keeping up with the management of supply chains in the silos departments in Baghdad, Including the silo of Khan Dhari with modern technologies), the importance of the research lies in showing how to employ quality engineering and rearrange the technical activities related to receiving grain. The most important results reached are the adoption of advanced strategies related to the processes of receiving the wheat crop and the reliance on an advanced electronic system in the work.